Pulmonary granulomas confirmed in Blau syndrome using TBLC specimens: Case report - Shimizu, Yasuo; Kushima, Yoshitomo; Tanaka, Ayae; Takemasa, Akihiro; Ishida, Kazuyuki; Niho, Seiji (Frontiers in Medicine, 2024)
Blau syndrome (BS), is an autoinflammatory granulomatosis disease characterized by a distinct triad of skin, joint, and eye disorders similar to those of sarcoidosis, but the lung involvement frequently observed in sarcoidosis are rare. Granulomas from patients with BS displayed a distinct morphology indicating an exuberant chronic inflammatory response. Patients with BS may have granulomatous lung lesions, which require early diagnosis. To determine whether therapeutic intervention is needed for lung lesions, examining transbronchial lung cryobiopsy specimens and accumulating cases of BS with lung involvement could be contributed to improving BS management in the future.